Cerebral Regional Homogeneity Alternation of Pregnant Women With Antenatal Depression During the Pandemic - Cheng, Bochao (Front Psychiatry, 2021)
Purpose: The COVID-19 epidemic has been a threat to the health of people all over the world. Various precautions during COVID-19 in China have kept a large number of people in isolation, and this has inconvenienced and placed enormous stress on pregnant women. Pregnant women are more likely to suffer from antenatal depression (ANDP) with social isolation or low social support. This research aims to investigate the neurobiological mechanisms underlying ANDP, which impedes early detection and intervention in this disorder. Methods: A total of 43 singleton pregnant women who experienced isolation were recruited, including 21 treatment-naïve ANDP patients and 22 healthy pregnant women (HPW). To explore the intrinsic cerebral activity alternations in ANDP using resting-state functional MRI (rsfMRI), we assessed the local regional homogeneity (ReHo) differences in two groups using the voxel-based whole-brain analysis. The correlation between the regional functional abnormalities and clinical variables in ANDP patients was also examined. Results: Compared with HPW, ANDP patients showed decreased ReHo in the left dorsolateral prefrontal cortex, right insular and the cluster coving the right ventral temporal cortex (VTC), amygdala (AMG), and hippocampus (HIP). The Edinburgh Postnatal Depression Scale (EPDS) scores of ANDP patients negatively correlated with the ReHo in the right VTC, AMG, and HIP. Conclusion: Elucidating the neurobiological features of ANDP patients during COVID-19 is crucial for evolving adequate methods for early diagnosis, precaution, and intervention in a future epidemic.